Surgery combined with controlled-release doxorubicin silk films as a treatment strategy in an orthotopic neuroblastoma mouse model - Chiu, B (Nature Publishing Group, 2014)
BACKGROUND: Neuroblastoma tumour resection goal is maximal tumour removal. We hypothesise that combining surgery with sustained, local doxorubicin application can control tumour growth. METHODS: We injected human neuroblastoma cells into immunocompromised mouse adrenal gland. When KELLY cell-induced tumour volume was >300 mm(3), 80–90% of tumour was resected and treated as follows: instantaneous-release silk film with 100 μg doxorubicin (100IR), controlled-release film with 200 μg (200CR) over residual tumour bed; and 100 and 200 μg intravenous doxorubicin (100IV and 200IV). Tumour volume was measured and histology analysed. RESULTS: Orthotopic tumours formed with KELLY, SK-N-AS, IMR-32, SH-SY5Y cells. Tumours reached 1800±180 mm(3) after 28 days, 2200±290 mm(3) after 35 days, 1280±260 mm(3) after 63 days, and 1700±360 mm(3) after 84 days, respectively. At 3 days post KELLY tumour resection, tumour volumes were similar across all groups (P=0.6210). Tumour growth rate was similar in untreated vs control film, 100IV vs 100IR, and 100IV vs 200IV. There was significant difference in 100IR vs 200CR (P=0.0004) and 200IV vs 200CR (P=0.0003). Tumour growth with all doxorubicin groups was slower than that of control (P: <0.0001–0.0069). At the interface of the 200CR film and tumour, there was cellular necrosis, surrounded by apoptotic cells before reaching viable tumour cells. CONCLUSIONS: Combining surgical resection and sustained local doxorubicin treatment is effective in tumour control. Administering doxorubicin in a local, controlled manner is superior to giving an equivalent intravenous dose in tumour control.